Therapeutic Boon or Hidden Bane? Semaglutide for Weight Loss in Non-diabetics - Aneesh Kumar Sangtiani; Iqra Qamar; Hassan Shamim; Farheen Siddiqui (Journal of Community Medicine and Health Solutions, 2026)
Semaglutide, a long-acting GLP-1 receptor agonist indicated for type 2 diabetes, has recently been approved by the US FDA for chronic weight management in non-diabetic obese patients. It works on GLP-1 receptors in the gut, pancreas, and hypothalamus to stimulate insulin release, decelerate stomach emptying, and augment satiety.Results from the clinical trials demonstrate that semaglutide provides a marked weight loss for obesity, approximately 10% of body weight (≈10 kg), with an average BMI drop of ~3.7 kg/m² and an 8.3cm decrease in waist circumference compared to the placebo. It also improves BP, lipids, and other cardio-metabolic parameters. Of note, Wegovy (semaglutide) is already cleared to lower the risk of major adverse cardiovascular events for overweight and obese patients with heart disease. The most frequent side effects are stomach-related (such as nausea, vomiting, diarrhea); less common, but serious side effects include acute pancreatitis, gallbladder disease, and thyroid C-cell tumors. It is expensive, about $1200–$1300 per month, restricting patient access.Semaglutide is beneficial in obesity therapy (a ‘boon’), resulting in significant weight loss and metabolic benefits. But its “bane” is tolerability, psychological burden, and costs. To achieve optimal benefit and minimize potential harm, semaglutide should be prescribed as part of an overall strategy for obesity care (with diet, exercise, and behavioral support); this will require careful patient selection and monitoring. Studies of its long-term safety, cost-effectiveness, and psychosocial effects should be a focus of future research and policy to establish that the benefits of semaglutide outweigh its detrimental consequences.